Implementasi makerspace sebagai pusat kreativitas dan inovasi di perpustakaan perguruan tinggi - M. Yusuf (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2023)
Traditional libraries adapt to changing times and play an increasingly important role in today's society. One of the innovations adopted by several libraries is Makerspace implementation. This study aims to analyze the role of the library as a center for creativity and innovation through a case study of Makerspace implementation. The literature review includes the concept of Makerspace, the role of libraries in creativity and innovation, and studies related to Makerspace implementation in libraries.he research method used is a case study approach with data collection through observation, interviews, and document analysis. The results of the description of the Makerspace implementation reveal the profile of the library that implements the Makerspace, the facilities and tools available, as well as the activities and programs held. Makerspace implementation analysis includes benefits and impacts in increasing creativity and innovation, challenges faced, and success factors. Through case studies on the successful implementation of Makerspaces, this research provides an overview of the program, community participation, and the results achieved. The conclusion of this study highlights the importance of libraries as centers of creativity and innovation through the implementation of Makerspaces. Implications and recommendations are presented to encourage other libraries to adopt creative and innovative approaches, such as Makerspaces. Although this research has limitations in terms of scope and time, it contributes to the development and evaluation of Makerspace implementation in libraries.